Council of Europe Standards in the Field of Probation - Batrićević, Ana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2013)
Being a member state of the Council of Europe, the Republic of Serbia is obliged to obey and implement European standards in the field of enforcement of criminal sentences, particularly alternative sanctions, in its national legislation, including the standards of probation, supervision and post-penal treatment. Accordingly, alterations of current and adoption of new laws and sub-legal acts relevant to the issue of execution of both institutional as well as community criminal sentences and measures are planned. These draft legal documents, adoption of which is still being expected, dedicate a significant amount of attention to the issue of probation, supervision and post-penal treatment of offenders as particularly approved and effective means of recidivism prevention and crime suppression. Therefore, the author of this paper analyzes the contents of the Recommendation CM/Rec (2010)1 adopted by the Committee of Ministers of the Council of Europe, which contains the so-called Probation Rules and which, together with other legal sources of this regional organization, comprises the network of European documents regulating the execution of criminal sentences. The author also highlights the necessity to harmonize the existing legal framework of the Republic of Serbia with the European as well as the need to provide conditions for its efficient practical application through establishing adequate agencies, improving the quality of work of existing services, education of present and recruitment of new professional staff members and granting resources sufficient for their regular functioning.